Broadband nanoplasmonic photodetector fabricated in ambient condition. (1st December 2022) - Banerjee, Debika; Asuo, Ivy; Fortier, François-Xavier; Pignolet, Alain; Cloutier, Sylvain G
Abstract: Surface plasmon are widely used to promote the exciton generation and light absorption in solar cells and photodetectors. In this work, a feasible approach for UV–vis-NIR photodetection using plasmon-enhanced silicon nanowires (SiNWs) and amorphous TiO2 heterostructure is presented. The photodetector shows excellent photo response up to 3.3 orders of magnitude enhancement with rise/decay times of 77/51 μ s. Under small external bias (1V), the photodetector exhibits very high responsivity up to 49 A W −1 over a broadband wavelength range from 300–1100 nm. All the experimental procedures are performed at room temperature in ambient conditions. Its simple fabrication route and excellent performance make this photodetector distinct from similar architectures. Our finding offers new opportunities to engineer plasmon-based nanostructures in chemical sensors, optoelectronics and nanophotonic devices and applications.